THE EFFECT OF CAPITAL INTENSITY AND GREEN ACCOUNTING ON TAX AVOIDANCE WITH CORPORATE SOCIAL RESPONSIBILITY AS A MODERATOR - Sitti Khadija; Iin Rosini; Dian Widiyati (ZILLZELL MEDIA PRIMA, 2025)
This study analyzes the determinants of corporate tax avoidance with focus on the roles of capital intensity and green accounting, and the moderation of corporate social responsibility (CSR) in the context of Indonesian healthcare companies. Using secondary data from annual and sustainability reports of 11 companies listed on the Indonesia Stock Exchange from 2020-2024, this research analyzes 55 panel data observations. The analysis method employs panel regression with common effect model after going through a series of model selection tests. The results reveal important findings: first, capital intensity does not significantly affect tax avoidance, indicating that fixed assets serve more for operational purposes than tax strategy. Second, green accounting has a significant positive effect on tax avoidance, showing the utilization of environmental costs to legally reduce tax burden. Third, CSR acts as a significant negative moderator in the relationship between capital intensity and tax avoidance, but is insignificant in moderating the relationship between green accounting and tax avoidance. These findings provide valuable contributions to the development of agency theory and sustainable corporate governance practices.